The SARS Epidemic in Hong Kong – A Human Calamity in the 21st Century - Lee, S. H. (Methods of Information in Medicine, 2005)
Purpose: This paper reviews the epidemiology and control measures of the SARS epidemic in Hong Kong. It sets out proposals for better preparedness to tackle the disease in future.Background: Severe Acute Respiratory Syndrome (SARS) started to strike Hong Kong in March 2003. A total of 1,755 SARS cases with 298 deaths were reported. Prior to the occurrence of the disease in Hong Kong, an intense outbreak of atypical pneumonia was reported in the nearby Guangdong Province in Mainland China.Results: There were three phases in the epidemic. The first phase in March 2003 involved a teaching hospital. The infection originated from a visiting professor from Guangdong, He developed SARS in Hong Kong and died in a Hong Kong hospital. The second phase in April was the spread of the infection from the hospital to the community. The third phase in May was the declining period which ended in June following the removal of Hong Kong from the list of infected areas by WHO.Conclusion: Hong Kong was ill prepared at the early stage of the epidemic. The epidemic produced not only health but also social, economic and humanitarian problems. The epidemic, however, created a strong sense of unity among all sectors of the population in the fight against the disease.
Keywords: SARS; epidemiology; etology; informatics; control; surveillance